A conspectus of legal recognition and protection of elderly rights in international law, Malaysian law and shariah perspectives - Mokhtar, Khairil Azmin (2016)
In the past years, the world has witnessed a remarkable interest in the elderly. Many international conferences and symposiums were held to deal with the issues and problems they encounter. There are almost six events created by UN related with ageing society namely: 1. Vienna International Plan for Ageing (1982) 2. UN Principles for Older Persons 3. International Day for Older Persons 4. UN Proclamation on Ageing 1992 5. International Year of Older Persons 1999 6. Madrid International Plan of Ageing 2002